Pengelolaan Keuangan Negara Berdasarkan Prinsip Legalitas dan Antikorupsi - Reski Apriyani; Putri Rahmawati; R. Nur Hafriza; Wahjoe Pangestoeti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
To ensure openness, responsibility and effectiveness in managing state finances, this research examines state financial management from a legality and anti-corruption perspective. In this research, relevant laws and regulations and scientific literature were studied using a literature study approach. The research results show that the principle of legality emphasizes the need for all state financial management activities to comply with relevant regulations, including the use of the State Revenue and Expenditure Budget (APBN) as a legal basis. The anti-corruption principle complements the principle of legality with preventive pressure and firm action against the protection of permits that are detrimental to state finances. These two principles support each other to ensure responsible financial management, protect officials with good intentions, and take action against perpetrators of corruption who fulfill the elements of malicious intent. In conclusion, implementing the principles of legality and anti-corruption synergistically can encourage good state financial governance, support clean government, and create sustainable development.